The relationship between foreign direct investment and the maturity of the real estate market: an assessment of investment activities of South African real estate companies with exposure on the African continent - Mahlaole, Tahane (Research of GSB, 2017)
Africa has begun to show tremendous socio-economic development and gradually improving market conditions. As a result, Africa's perceived attractiveness has improved as new investment frontiers are sought. It has become crucial that current and future economic and market growth needs can be met by infrastructure and real estate development. In order for the various real estate markets to develop further, they would need to attract a significant amount of capital expenditure, of which a portion may come from institutional investors. In order to achieve this, Africa needs to ensure that the desired investment environment is stimulated in the real estate market so as to redirect some of the capital flows into improving and increasing current and future real estate stock on the continent. This dissertation focuses on real estate in Africa by assessing the nature of the relationship between the maturity of real estate markets and foreign direct investments. It does so by assessing the investment decisions of South African real estate investors with exposure in the rest of the continent. The research findings seek to provide insight into the nature of the relationship and further assess its level of importance for South African real estate investors. Key findings were that maturity of real estate markets correlated poorly with investment activities and investors priorities when making investment decisions. However, maturity is a factor in real estate investment decisions. The aim was to assess the minimum level of maturity that was required for South African investors before entering a market; however, it became clear that mature markets or very immature markets are not necessarily what investors seek. An element of the risk/return profile is influenced by the maturity of markets: the less mature markets have the greater level of risk and the more mature markets have very little risk in comparison.